Intraoperative Imaging in Orbital and Midface Reconstruction - Wilde, Frank; Schramm, Alexander (Facial Plastic Surgery, 2014)
The orbit is very often affected by injuries which can leave patients not only with esthetic deficits, but also with functional impairments if reconstruction is inadequate. Computer-assisted surgery helps to achieve predictable outcomes in reconstruction. Today, intraoperative three-dimensional (3D) imaging is an important element in the workflow of computer-assisted orbital surgery. Clinical and radiological diagnosis by means of computed tomography is followed by preoperative computer-assisted planning to define and simulate the desired outcome of reconstruction. In difficult cases, intraoperative navigation helps in the implementation of procedure plans at the site of surgery. Intraoperative 3D imaging then allows an intraoperative final control to be made and the outcome of the surgery to be validated. Today, this is preferably done using 3D C-arm devices based on cone beam computed tomography. They help to avoid malpositioning of bone fragments and/or inserted implants assuring the quality of complex operations and reducing the number of secondary interventions necessary.
Keywords: intraoperative imaging; orbital wall fracture; orbital reconstruction; intraoperative navigation; computer-assisted surgery